Making pigment of blue jeans and its application to thermal energy harvesting - Ekanayaka Ekanayaka Mudiyanselage Hemal Dilanga (Nanyang Technological University, 2023)
Low grade heat energy is the most abundant form of heat energy in the world, and it is easily wasted due to the inability to harvest it efficiently and cost effectively. Recent up trend in clean energy harvesting has led to revisit the potentials of low-grade heat harvesting and Prussian blue analogues have shown promising results as PBAs (Prussian Blue Analogue) are environmentally friendly and they are easy to synthesis, so they have become popular recently in the research on electrical storage devices[1]. A good application of these low-grade heat harvesting is automobile industry and industries generating massive amounts of low-grade heat[2]. The focus on harvesting this low-grade heat energy lies between an efficient and cost-effective system and it is achievable through “thermal regenerative electro-chemical cycle” which uses the physics of different potentials at different temperatures. And Prussian blue analogs can succeed in this with the evidence that is available so far. And it will come to commercial use in the near future[3]